Isotope abundance ratio measurements using femtosecond laser ablation ionization mass spectrometry. (1st October 2020) - Tulej, Marek; Neubeck, Anna; Riedo, Andreas; Lukmanov, Rustam; Grimaudo, Valentine; Ligterink, Niels F.W.; Ivarsson, Magnus; Bach, Wolfgang; de Koning, Coenraad; Wurz, Peter
Abstract: Accurate isotope ratio measurements are of high importance in various scientific fields, ranging from radio isotope geochronology of solids to studies of element isotopes fractionated by living organisms. Instrument limitations, such as unresolved isobaric inferences in the mass spectra, or cosampling of the material of interest together with the matrix material may reduce the quality of isotope measurements. Here, we describe a method for accurate isotope ratio measurements using our laser ablation ionization time‐of‐flight mass spectrometer (LIMS) that is designed for in situ planetary research. The method is based on chemical depth profiling that allows for identifying micrometer scale inclusions embedded in surrounding rocks with different composition inside the bulk of the sample. The data used for precise isotope measurements are improved using a spectrum cleaning procedure that ensures removal of low quality spectra. Furthermore, correlation of isotopes of an element is used to identify and reject the data points that, for example, do not belong to the species of interest. The measurements were conducted using IR femtosecond laser irradiation focused on the sample surface to a spot size of ~12 μm. Material removal was conducted for a predefined number of laser shots, and time‐of‐flight mass spectra were recorded for each of the ablated layers. Measurements were conducted on NIST SRM 986 Ni isotope standard, trevorite mineral, and micrometer‐sized inclusions embedded in aragonite. Our measurements demonstrate that element isotope ratios can be measured with accuracies and precision at the permille level, exemplified by the analysis of B, Mg, and Ni element isotopes. The method applied will be used for in situ investigation of samples on planetary surfaces, for accurate quantification of element fractionation induced by, for example, past or present life or by geochemical processes.